Experiences During Extensive Reading Program For English Department Students - Ardiansyah, Farhan Tri (RETAIN, 2021)
Extensive Reading is deemed essential for freshmen of English Department as it helps to improve students’ reading skills especially comprehension. Joining the Extensive Reading program assigned in early college years helps elevate students’ reading comprehension skills and increase their vocabulary size. This article aims to explore students’ experiences with the Extensive Reading program based on their perceived appraisal on; 1) time allocation during extensive reading, 2) potential obstacles found during extensive reading as well as 3) the length of text used as reading materials. This study took English Department’s students as its subject. The answers gained from 45 respondents of Extensive Reading Experience questionnaire were later analyzed in descriptive and thematic fashion to form practical suggestions for college students and lecturers. In addition, this article can also be used to identify the benefits and drawbacks of the Extensive Reading program provided by English Department. The results of the study in general showed that; 1) English Department’s students regard the time allocation as sufficient for completing extensive reading assignments, 2) the obstacle that hinders the development of comprehension skills in reading the most is difficult vocabulary and 3) long, interesting texts can increase student motivation to read extensively. Further recommendations would be served at the end of the article.